Highly sensitive procedure for the determination of ultra-trace amounts of bromate ions in water by dispersive liquid-liquid microextraction combined with UV-Vis spectrophotometry - Al-Saidi, Hamed Mohammed (European Journal of Chemistry, 2012)
In the present work, a novel, simple, and green procedure is presented for the determination of bromate ions in water. The method is based upon using tetraphenylphosphonium iodide (TPP+ I−) as an ion pairing reagent and a source of iodide ions that react with bromate to produce triiodide ion (I3−). The complex ion associate formed between I3−, equivalent to bromate ions, and TPP+ was extracted by dispersive liquid-liquid microextraction. Under the optimum conditions, Beer’s-Lambert law and Ringbom’s plot of the colored complex ion associate were obeyed in the range of 0.01-0.5 and 0.02-0.2 µg/mL of BrO3− at 365 nm, respectively, with a relative standard deviation in the range of 2.1 ± 1.3%. The proposed method offers 0.003 and 0.012 µg/mL lower limits of detection (LOD) and quantification (LOQ) of the bromate ion, respectively. Moreover, the chemical composition and the stability constant of the developed ion associate were found to be [TPP+ I3−] and 4.43 × 105, respectively. The proposed method was free from most interferences present in many chromatographic, spectrofluorimetric and spectrophotometric methods. The developed method did not need a special treatment of sample for eliminating the interferences prior to the application of DLLME and was successfully used to the analysis of bromate ion in both drinking water treated by ozone and tap water.